2014
DOI: 10.1002/pri.1585
|View full text |Cite
|
Sign up to set email alerts
|

‘Tell Me About Your Troubles’: Description of Patient-Physiotherapist Interaction During Initial Encounters

Abstract: This exploratory study examines the interaction between patients and physiotherapists during initial encounters and identifies assumptions underlying pain assessment that shape the therapists' exploration of patients' pain experience. It also shows evidence of the physiotherapists' difficulties to inquire about the patient's perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
0
15
0
2
Order By: Relevance
“…Accessible, attentive care and the physical and psychosocial environment are important aspects in establishing an empowering atmosphere, which is understood as a recognition of the patient's needs [29,30]. Opsommer and Schoeb [31] stated that the importance of communication arises from assumptions about how information should be transmitted, how questions are designed and how treatment interventions are recommended to patients. Our results also correspond well with the ideas of Opsommer and Schoeb [31], who state that collaboration, participation, negotiation and taking the patient's perspective into account are salient aspects of effective communication.…”
Section: Discussionmentioning
confidence: 99%
“…Accessible, attentive care and the physical and psychosocial environment are important aspects in establishing an empowering atmosphere, which is understood as a recognition of the patient's needs [29,30]. Opsommer and Schoeb [31] stated that the importance of communication arises from assumptions about how information should be transmitted, how questions are designed and how treatment interventions are recommended to patients. Our results also correspond well with the ideas of Opsommer and Schoeb [31], who state that collaboration, participation, negotiation and taking the patient's perspective into account are salient aspects of effective communication.…”
Section: Discussionmentioning
confidence: 99%
“…Documented communication features of a patient-centred approach such as open questions, minimal interruptions, and shared decision making (Bensing, 2000), were not overtly incorporated into observed physiotherapy treatment encounters. Other scholars of physiotherapy communication have also reached similar conclusions about the predominance of communication that represents biomedical and practitioner-centred approaches (Cruz et al, 2012;Josephson, Woodward-Kron, Delany, & Hiller, 2015;Opsommer & Schoeb, 2014).…”
Section: Does Communication In Physiotherapy Practice Align With the mentioning
confidence: 65%
“…For example, research from Denmark and the United Kingdom demonstrated that decisions within treatment sessions are made by physiotherapists with minimal patient involvement (Dierckx, Deveugele, Roosen, & Devisch, 2013;Jones et al, 2014). Other communication research has shown that physiotherapists drive goal-setting processes ; talk twice as much as patients ; use closed questions (Cruz, Moore, & Cross, 2012;Opsommer & Schoeb, 2014); focus predominantly on pain and understanding the clinical condition (Cruz et al, 2012;Opsommer & Schoeb, 2014); and limit incorporation of the patient perspective (Josephson & Bülow, 2014;Opsommer & Schoeb, 2014).…”
Section: (Study 2 Treatment Encounter 17)mentioning
confidence: 99%
“…Some consultations start with open-ended questions (e.g. "Tell me") [29,52] but opening and follow-up questions are frequently closed-ended and category-constrained (e.g. "So when did you fi:rst have these attacks") [28,29,43,52].…”
Section: Information Gatheringmentioning
confidence: 99%
“…"Tell me") [29,52] but opening and follow-up questions are frequently closed-ended and category-constrained (e.g. "So when did you fi:rst have these attacks") [28,29,43,52]. By doing this, healthcare providers control what information is relevant for them [29,30] and when patients' answers suffice, e.g.…”
Section: Information Gatheringmentioning
confidence: 99%